Graphdiyne-Coated Microfiber All-Optical Temporal Modulator Based on Saturable Absorption - Zhang, Kuokuo; Qiu, Zeping; He, Shijia; Bao, Wenli; Lu, Shunbin (Frontiers in Physics, 2022)
High speed all-optical modulator is a key device in next generation communication systems. Due to easy fabrication and effective modulation effect, two dimensional (2D) materials-microfiber structure all-optical modulators arouse much attention. Graphdiyne (GDY) is an excellent nonlinear optical material and expected to utilize in all-optical modulators. In this work, we demonstrate a GDY-coated all-optical temporal modulator according to its saturable absorption. Under the pump pulse light of 1064 nm, the fabricated modulator successfully modulates the continuous-wave (CW) light of 1550 nm to the waveform of pump light with a pulse width of 4 ns and repetition rate of 5 kHz. Our results show that GDY could be used in high speed all-optical modulators and pave a way for the research of GDY in all-optical information processing applications.